PENGARUH TUMBUHAN KABOMBA (Cabomba aquatica Aubl.) TERHADAP KADAR LOGAM BESI (Fe) DAN TEMBAGA (Cu) LIMBAH CAIR LABORATORIUM KIMIA FMIPA UNTAN - Hanafi Afriza; Mukarlina Mukarlina; Diah Wulandari Rousdy (Teknik Lingkungan Universitas Islam Indonesia, 2020)
Laboratory liquid waste contains several hazardous materials such as heavy metals generated from laboratory activities. One of treatment method used to treat laboratory liquid waste is fitoremediation using Kabomba plants (Cabomba aquatica Aubl). This research aims to determine the ability of Kabomba (Cabomba aquatica, Aubl.) to reduce the heavy metal content of liquid waste (Fe and Cu) from the Chemistry Laboratory of FMIPA Untan. This research used a Completely Randomized Design consisting of five treatments of waste concentration: control, 25%, 50%, 75%, 100%. Based on the results of the research, the Kabomba (Cabomba aquatica, Aubl.) plants was able to absorb more iron (Fe) than copper (Cu) metal with the highest concentration at the implementation of 75% concentration. Kabomba plants can reduce Fe contain in wastewater by 56.61% with an absorption value of 144.87 mg/l.Key Words : Kabomba (Cabomba aquatica Aubl), Laboratory Liquid Waste, Iron (Fe), Copper (Cu).